TINGKAT PENGETAHUAN DAN SIKAP KELUARGA PASIEN TERHADAP PERILAKU PENCEGAHAN INFEKSI NOSOKOMIAL - Vevi Kurniawati (Akper Kesdam I/Bukit Barisan Padang, 2022)
Nosocomial infection is an infection obtained from the hospital or when the patient is admitted to the hospital, where the infection occurs 3 x 24 hours after the patient is admitted to the hospital. Nosocomial infections can be caused by bacteria, viruses, fungi or parasites. In Indonesia, the incidence of nosocomial infections is still relatively high. Efforts are being made to reduce the incidence of nosocomial infections by knowing and implementing nosocomial infection prevention. The purpose of this study was to determine the knowledge, attitudes, and actions of families of inpatients at RS TK.III dr. Reksodiwiryo Padang on prevention of nosocomial infections. This research is a quantitative research, with a total sample of 88 people. The data in this study are primary data obtained through questionnaires about knowledge, attitudes and actions regarding nosocomial infection prevention behavior in hospitals. The data obtained is processed and analyzed and then presented in the form of a frequency distribution table. The results of this study found that the level of knowledge of respondents was in the less category as many as 53 people (60.2%), the attitudes of respondents were in the less category, namely as many as 53 people (60.2%) and the actions of respondents were in the less category, namely as many as 50 people (56.8%). The conclusion in this study is the knowledge, attitudes and actions of the families of inpatients at Tk.III Hospital, dr. Reksodiwiryo Padang regarding the behavior of preventing nosocomial infections is classified as lacking and counseling can be given to improve the behavior of the patient's family towards preventing infection in the hospital.